The Immunomodulatory, Nitric Oxide and Cytokine activity of SeptilinTM - Hoosen, Mujeeb (Bangladesh Journal of Medical Science, 2019)
Objective: Herbal immunomodulatory preparations are increasing in popularity. In vitro, in vivo and clinical trial studies are needed to ensure safety, quality and efficacy of these herbal medicines. SeptilinTM, a proprietary herbal medicinal product has been reported to have immunomodulatory effects. Methods: For this narrative review the author surveyed the primary literature on SeptilinTM and its ingredients with regards to immunomodulatory, nitric oxide (NO) and cytokine activity. Databases utilized included Pubmed, Science Direct and EBSCO, Google Scholar as well as a hand search through journals and bibliographies was included. English language restriction was observed. The following parameters had to be met for study inclusion: investigations on SeptilinTM as a formulation (liquid or dried form) were accepted. Research on the isolated constituents of SeptilinTM (single herbs) was also accepted. The accepted model types included; in vitro and in vivo, animal and human models. The following were also required; method of preparation of the SeptilinTM, concentration of the plant preparation and dose/exposure time. Only studies providing statistically significant results with regards to immunomodulatory, cytokine and nitric oxide activity were included. Results: SeptilinTM and its ingredients had effects on at least one cytokine. The most frequently studied cytokines were IL-1, IL-2, IL-4, IL-6, TNF, and IFN. Many studies also reported on NO activities. SeptilinTM and its ingredients demonstrated modulation of several cytokines with varying results on NO activity. The bulk of studies conducted on SeptilinTM and its ingredients were in vitro, the few in vivo studies were mainly conducted in rats or mice models with a few studies conducted on humans. Conclusion: The in vitro and in vivo research demonstrates that SeptilinTM and its ingredients modulate the secretion of multiple cytokines and NO with varying effects on cytokine and NO secretion due to divergent research methodologies. The reported therapeutic success of these herbal products by natural medicine practitioners and clinicians may be due to their effects on cytokine and NO activity. Bangladesh Journal of Medical Science Vol.18(4) 2019 p.675-688